Modification of conductive material AA6101 of OPGW conductors against lightning strikes - Karabay, Sedat (Strojniški vestnik, 2013)
In this article, failure in lightning tests and the overcoming of its destructive effects by improving the new generation of optical grounding wire (OPGW) are presented. The designed composite structure for transmission lines in Turkey is composed of six galvanized steel wires, one stainless steel tube with multiple glass fibres and 12 aluminium alloy AA6101 wires. Test samples from prototype OPGW successfully passed short circuit requirements but failed in tests of lightning strikes. Consequently, a material modification was applied by feeding 3% AlB2 master alloy as a 9.5 mm rod into molten metal in the tundish when the metal flows from the melting furnace to the vertical log casting mould. Logs cast from AA6101 are used to manufacture feedstock by means of extrusion press. Impaired electrical conductivity of the AA6101 due to the presence of heavy metal impurities such as Ti, Cr and V should be increased to pass the tests. Following this, the transition metals were transformed into insoluble borides from solution after inoculation with AlB2. As a result, the conductivity of wires drawn from feedstock produced by extrusion press with the modified AA6101 billets was increased from 52.5 to 57% IACS. Consequently, the modified OPGW with AlB2 satisfied the requirements of international standards related to lightning tests.
Keywords: AA6101 feedstock; AlB modification; conductivity; električna prevodnost; lightning strike; modifikacija z AlB2; optical ground wire; pretrganje žice; samonosni optični kabel OPGW; surovec iz AA6101; udar strele; wire breakage